The role of the judge in providing evidence in international commercial arbitration - غزال, عبد اللطيف (Latakia University Journal - Economic and Legal Sciences Series, 2025)
Arbitration plays a pivotal role in the field of international trade, due to its many advantages that have made it a haven for resolving disputes related to international trade. However, arbitration still lacks the element of coercion and obligation when the issue is related to providing evidence or forcing the parties to facilitate access to it. In this case, the arbitration body must resort to the competent judiciary to assist it in forcing one of the parties or others to provide evidence and thus provide the sound basis on which the arbitrator will build his decision. This research will address the issue of the role assigned to the judge in providing evidence to the arbitration body by examining the most important means of proof in which this role is manifested, which are testimony and expertise.